Answer:
$188.75
Step-by-step explanation:
His earnings were ...
$80 + 0.15 × $725 = $80 +108.75 = $188.75
Jerome earned $188.75 last weekend.
Answer:
1 whole one and a third of one.
Step-by-step explanation:
1 1/3 of a granola bar
Answer: 1.33333333333 or 1.3 as a repeating decimal
Just divide 8 ÷ 6
If a student is randomly selected from the group, what is the probability that they are majoring in both math and science? Round your answer to the nearest whole percent.
Answer:
Step-by-step explanation:
Since, The total number of student = 300
Out of which,
The number of students who are only in Maths = 120
And, The number of students who are only in Science = 50
While, the students who are not from any subject = 100
Hence, the number of student who are from both maths and science = Total student - Maths student (only) - science student (only) - None
= 300 - 120 - 50 - 100
= 30
That is, there are 30 students who are both from science and maths,
Thus, the probability of selecting one student who is both from maths and science = 30/300 = 1/10
A.
p = 40
B.
p = 100
C.
p = 28
D.
p = 1
i think that it's c.
Answer:
(a) F(x) = 2x^2 - x - 1
Step-by-step explanation:
The quadratic regression function of a graphing calculator does this nicely.
The one attached shows the function to be ...
F(x) = 2x^2 -x -1
__
Additional comments
The supplied point (0, -1) tells you the y-intercept is -1. That means the constant in the function's equation will be -1. Only one answer choice has that.
F(x) = 2x^2 -x -1
__
As always, the first step in problem solving should be to look at the problem, and look at the available solution choices. Understanding these things will generally allow you to throw out answer choices that don't provide a sensible answer to the question. Here, that leaves you with only one answer choice, which is all you need.
Answer:
The simplified form of given expression is
Step-by-step explanation:
Given: Expression
We have to write the given expression in simplified form,
Consider the given expression
Divide the numbers
we get,
Apply exponent rule ,
we get,
Cancel y term, we have,
Thus, The simplified form of given expression is
Answer:
Step-by-step explanation:
The given expression is:
We have to simplify the above given expression.Thus,
Firstly, divide the constant terms, we get
Now, applying the exponent law, that is , we have
Thus, the simplified form of the above given equation is: